2018
DOI: 10.1038/s41598-018-32016-x
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of miRNAs by reconstituted high-density lipoproteins in diabetes-impaired angiogenesis

Abstract: Diabetic vascular complications are associated with impaired ischaemia-driven angiogenesis. We recently found that reconstituted high-density lipoproteins (rHDL) rescue diabetes-impaired angiogenesis. microRNAs (miRNAs) regulate angiogenesis and are transported within HDL to sites of injury/repair. The role of miRNAs in the rescue of diabetes-impaired angiogenesis by rHDL is unknown. Using a miRNA array, we found that rHDL inhibits hsa-miR-181c-5p expression in vitro and using a hsa-miR-181c-5p mimic and antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…In this investigation, miRNA-hub gene regulatory network and TF-hub gene regulatory network were constructed and analyzed. Demirsoy et al [228], Hourigan et al [229], Safar et al [230], Zmuda et al [231], Boese et al [232] and Suhara et al [233] found that hsa-mir-200a-3p, hsa-mir-181c-5p, VDR (vitamin D receptor), ATF3, PAX6 and RPTOR (regulatory associated protein of MTOR complex 1) were participating in the occurrence and development of T2DM. Cabiati et al [234] and Patankar et al [235] proved that hsa-mir-410-3p and GATA4 mediate the development of obesity, but these genes might be associated with development of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, miRNA-hub gene regulatory network and TF-hub gene regulatory network were constructed and analyzed. Demirsoy et al [228], Hourigan et al [229], Safar et al [230], Zmuda et al [231], Boese et al [232] and Suhara et al [233] found that hsa-mir-200a-3p, hsa-mir-181c-5p, VDR (vitamin D receptor), ATF3, PAX6 and RPTOR (regulatory associated protein of MTOR complex 1) were participating in the occurrence and development of T2DM. Cabiati et al [234] and Patankar et al [235] proved that hsa-mir-410-3p and GATA4 mediate the development of obesity, but these genes might be associated with development of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Using EC culture, a zebrafish model for vascular growth, and hypercholesterolemic LDLr -/- mice as a model of impaired vascular growth, we found much lower angiogenesis with dHDL than with nHDL. There is much evidence showing that miRNAs regulate angiogenesis and that HDL and reconstituted HDL can carry and deliver miRNAs to cells [ [43] , [44] , [45] , [46] , [47] ]. We found that miRNA profiles in ECs differed between nHDL and dHDL treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies demonstrate that HDL promotes angiogenesis by activating the Ras/ERK pathway or Src/PI3K/AKT-ERK/Rac pathway, or S1P3-dependent of VEGFR2 pathway, which is independent of HDL cargo molecules [ [3] , [4] , [5] ]. Recently it also shows that reconstituted HDL mediates angiogenesis in diabetes by regulating miRNAs [ 47 ]. However, it is unclear whether native HDL regulates these pathways via miRNAs regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also found a negative correlation between this miRNA and high-density lipoprotein (HDL) post-intervention, it is already known that HDL has a role in transporting endogenous miRNAs and delivering them to recipient cells with functional targeting capabilities [ 14 ]. MiRNAs, specifically miR-92a was seen to be involved in the regulation of angiogenesis and transported within HDL to sites of injury/repair [ 44 ].…”
Section: Discussionmentioning
confidence: 99%